Shifting from paper-and-pencil to computer-based testing: Requisites, challenges, and consequences for testing outcomes – A Croatian perspective - Buško, Vesna (Array, 2009)
The paper focuses on prospects of moving from paper-and-pencil to computer-based testing, pointing also at basic conditions required to facilitate decision-making and bring about desired changes in the assessment, and consequently in teaching practices and essential learning and educational outcomes. Prevailing practices in psychological assessment and testing in Croatia are shortly outlined. Potential barriers in implementing ICT in the assessment processes are discussed including knowledge or informational, organizational, policy and financial issues. The reflections on benefits and likely obstacles to transition to computer based assessment are exemplified by recent experiences from large-scale testing projects, such as national curriculum tests and PISA 2006 in Croatia.